1988
DOI: 10.1182/blood.v71.5.1234.1234
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus associated B cell lymphoproliferative disorders following bone marrow transplantation

Abstract: B cell lymphoproliferative disorders (BLPD) developed in eight patients following bone marrow transplantation (BMT) for leukemia (five patients) or immunodeficiency (three patients). Recipients of T depleted marrow from a mismatched donor were at particularly high risk of this complication. Six of 25 (24%) recipients of mismatched T depleted bone marrow developed BLPD. In contrast, none of 47 matched T depleted transplants, one of ten (10%) who received non-depleted marrow from an unrelated donor, and only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(66 citation statements)
references
References 0 publications
3
63
0
Order By: Relevance
“…They also found that higher risks of PTLD were linked to the method of T-cell depletion that selectively targeted T cells or T plus natural killer cells, rather than those that removed both T and B cells (Curtis et al, 1999). Similar risk factors have been identified by others (Shapiro et al, 1988;Witherspoon et al, 1989;Bhatia et al, 1996;Gerritsen et al, 1996;Socie et al, 2000) and additionally include a diagnosis of primary immunodeficiency (Bhatia et al, 1996). Fourteen per cent of children transplanted with non-HLA-identical grafts, mainly for primary immunodeficiency and other congenital diseases and leukaemia, developed LPD compared with none after HLA-identical transplants (Gerritsen et al, 1996).…”
Section: Risk Factors For Ptldsupporting
confidence: 61%
“…They also found that higher risks of PTLD were linked to the method of T-cell depletion that selectively targeted T cells or T plus natural killer cells, rather than those that removed both T and B cells (Curtis et al, 1999). Similar risk factors have been identified by others (Shapiro et al, 1988;Witherspoon et al, 1989;Bhatia et al, 1996;Gerritsen et al, 1996;Socie et al, 2000) and additionally include a diagnosis of primary immunodeficiency (Bhatia et al, 1996). Fourteen per cent of children transplanted with non-HLA-identical grafts, mainly for primary immunodeficiency and other congenital diseases and leukaemia, developed LPD compared with none after HLA-identical transplants (Gerritsen et al, 1996).…”
Section: Risk Factors For Ptldsupporting
confidence: 61%
“…In contrast to results reported for post-transplant patients [26], it has been shown that a high EBV viral load may not always be associated with the increased occurrence of EBVassociated malignancy [27]. For instance, the high EBV viral load that is observed frequently after HIV infection has no predictive value for the occurrence of AIDS-related non-Hodgkin's lymphoma [28].…”
Section: Discussionmentioning
confidence: 79%
“…Virus-induced transformation of infected cells is associated with various malignant diseases [3][4][5][6]. EBV-associated lymphoproliferative disease has been observed in patients with X-linked lymphoproliferative disease [7] and those receiving intensive immunosuppressive therapy, such as bone marrow transplantation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%